The use of antimicrobials in Italian buffalo farms - Gabriele Di Vuolo; Federico Scali; Claudia Romeo; Valentina Lorenzi; Chiara D. Ambra; Maria Serrapica; Giovanna Cappelli; Francesca Fusi; Esterina De Carlo; Giovanni Loris Alborali; Luigi Bertocchi; Domenico Vecchio (Revista Científica)
Antimicrobial resistance (AMR) is a major global health emergency; 25,000 people die each year in Europe from infections sustained by resistant bacteria. Inappropriate antimicrobial use (AMU) in humans and animals is reinforcing AMR, threatening public health. The European Medicines Agency (EMA) has classified antimicrobials according to their importance in human medicine. Specifically, the EMA’s Category B refers to critical antimicrobials that are registered for use in animals but should only be administered in the absence of viable alternatives. Therefore, there is growing institutional attention to implementing actions for the optimization of AMU. In particular, the World Health Organization’s Global Plan of Action on Antimicrobial Resistance recommends a close intersectoral collaboration between public health and animal health (One Health). The purpose of this study was to report the first data on AMU in Italian dairy buffalo farms and the principal causes of treatment. Data from 102 farms were collected over a three-year period (2015-2017); AMU was estimated separately by age group (adults, heifers and calves) using the Defined Daily Dose for Italy (DDDAit). Antimicrobials were used almost exclusively on adults, where overall AMU was relatively low, averaging 1.72 DDDAit/head. The three most common causes of AMU in adult buffaloes were: urogenital (39.2%), dry cow therapy (26.2%), and mastitis (22.8%). The main molecules used are represented by tetracyclines followed by III- IV generation cephalosporins (III-IVGenCep) and I-II generation cephalosporins. With regard to the use of the categories of critical drugs (III-IV-GenCep and Quinolones), most of the use (65,4%) is linked to adult animals, while in relation to the ratio between DDDAit from critical drugs/total DDDAit for each category of animals, the values relating to calves are high (31.29%), proving that, even if fewer drugs are used, the incidence of criticals in this category should be reduced. Although direct comparisons may have some limitations, AMU seems to be lower in buffalo than in other species reared in Italy as reported in the bibliography (Mazza et al. 2021). The identification of the principal causes of AMU in buffalo represents an important step towards a more efficient AMU analysis of structural and management critical aspects connected to the buffalo breeding system finalized to reduce to sustainable mode the AMU, in particular critical antimicrobials, and their connected AMR.